2022
DOI: 10.1002/lt.26479
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fractional donor‐derived cell‐free DNA during subclinical graft injury after liver transplantation

Abstract: Personalized immunosuppression (IS) promises to improve the balance of necessary control of alloreactivity and dose-dependent adverse effects of long-term IS such as kidney insufficiency, infections, and malignancies. The majority of liver transplantation (LT) recipients exhibit graft injuries (graft inflammation and/or fibrosis) that are not eligible for an IS reduction according to current Banff criteria, even when liver enzymes are normal or only marginally elevated. This cross-sectional study evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…CXCL8 is a noninvasive marker that is relatively effective in diagnosing SCR. In addition, plasma levels of donor-derived free DNA are significantly higher in recipients with subclinical rejection than in recipients with no histological evidence of rejection after LT. 19 However, because of its relatively low sensitivity and specificity in the diagnosis of SCR, the application value of CXCL8 was limited. A recent study found that miR-181a-5p and miR-155-5p in plasma could jointly predict the occurrence of SCR with sensitivity and specificity of up to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8 is a noninvasive marker that is relatively effective in diagnosing SCR. In addition, plasma levels of donor-derived free DNA are significantly higher in recipients with subclinical rejection than in recipients with no histological evidence of rejection after LT. 19 However, because of its relatively low sensitivity and specificity in the diagnosis of SCR, the application value of CXCL8 was limited. A recent study found that miR-181a-5p and miR-155-5p in plasma could jointly predict the occurrence of SCR with sensitivity and specificity of up to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, fractional dd-cfDNA was tested during subclinical graft injury after liver transplantation confirmed by surveillance biopsies (Baumann et al, 2022). The lower limit of quantification was 0.15% and the interassay CV ranged from 3% to 5.4%.…”
Section: Clinical Validity Of Donor-derived Cell-free Dna In Transpla...mentioning
confidence: 99%
“…In liver transplantation, the ddcfDNA is a powerful reference for the prediction and diagnosis of subclinical TCMR and overt TCMR and for the rapid diagnosis of graft-versus-host disease and monitoring of response to treatment. [48][49][50] However, as a product of allograft injury, the ddcfDNA is not rejection specific, its elevations can also be observed due to other causes, such as ischemia, trauma, and infection. [51] In renal transplantation, to achieve accurate detection of the alloresponse resulting in graft damage and benefit the individualized IS, the ddcfDNA is being tested in combination with other immunological strategies, including HLA epitope donor matching, T cell receptor sequencing, deep cytometric phenotyping of immune cell subsets, and routine DSA monitoring.…”
Section: Discussionmentioning
confidence: 99%